2005
DOI: 10.1590/s0004-27302005000200022
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism due to secretion of human chorionic gonadotropin in a patient with metastatic choriocarcinoma

Abstract: A 26-year-old pregnant woman presenting with repeated episodes of vaginal bleeding, weight loss, and shortness of breath was diagnosed with choriocarcinoma with metastases to both lungs. Chorionic gonadotropin levels (hCG) were >2.5 x 10 6 mU/mL. Consistent with hCGinduced subclinical hyperthyroidism, she had a suppressed TSH of 0.037mU/L (0.49 -4.67), a T4 of 18.1µg/dL (4.9 -10.7), and T3 of 136ng/dL (45 -137). Chemotherapy with a combined regimen with etoposide, methotrexate, and dactinomycine was started. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…In the following years, several reports substantiated the observation of hyperthyroidism in patients with trophoblastic tumors [2][3][4][5][6]. Giralt et al [5] reported hyperthyroidism in 7 out of 17 male patients with germ cell cancer and hCG levels of higher than 50,000 IU/l.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the following years, several reports substantiated the observation of hyperthyroidism in patients with trophoblastic tumors [2][3][4][5][6]. Giralt et al [5] reported hyperthyroidism in 7 out of 17 male patients with germ cell cancer and hCG levels of higher than 50,000 IU/l.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our clinical experience in treatment of testicular cancer and in light of the work reported by Madersbacher et al [7], it seems that in hCG-producing non-seminomatous germ cell tumors even excessively elevated hCG does not necessarily induce hyperthyroidism. While hyperthyroidism due to malignancy (trophoblastic tumors, hydatidiform moles, choriocarcinoma or testicular cancer) is a rare event, the prevalence of hCG-induced clinically manifest hyperthyroidism during pregnancy is about 0.05-0.2% in some series and up to 1% in others [6,8]. Even more so, according to Glinoer et al [8], close to 20% of pregnant women will have suppressed TSH, 2% will have suppressed TSH with increased thyroxin, and approximately 1% of pregnant women will have suppressed TSH, increased thyroxin and clinical signs of hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Korelasi antara kadar HCG dan beratnya derajat metabolik hipertiroid adalah 25.000 U/L HCG setara dengan 1 mU/L aktivitas TSH. 16 Untuk membedakan mola hidatidosa dengan kehamilan normal dapat dengan melihat perbedaan kadar HCG total di dalam darah. Van Trommel dkk.…”
Section: Pendahuluanunclassified